PELATIHAN MENDELEY DAN TEKNIK ANALISIS DATA DENGAN EVIEWS - Husain Nurisman; Dian Surya Sampurna; Tutty Nuryati; Joko Bagio Santoso; Toto Aminoto; Bagus Styoko Purwo (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2022)
Pengabdian Kepada Masyarakat (PKM) is one of the three dharmas of university education, or the major responsibility of lecturers. This PKM activity is open to students completing their last year at private universities. PKM activities include the evaluation of